PENAFSIRAN KONSTITUSI TERHADAP PUTUSAN NOMOR 116/PUU-XXI/2023 TENTANG AMBANG BATAS PARLEMEN - ADY SUPRYADI; AESTHETICA FIORINIMANTIKA; RENA AMINWARA; FAHRURROZI FAHRURROZI; IMAWANTO IMAWANTO (Universitas Mahasaraswati K. Mataram, 2024)
The aim of this research is to find out and analyze the constitutional interpretation of Decision Number 116/PUU-XXI/2023 concerning parliamentary thresholds. The method used in this research is normative legal research with a statutory approach and a conceptual approach. The results of this research show that the Constitutional Court through Decision Number 116/PUU-XXI/2023 partially granted the application for material review submitted by the Association for Elections and Democracy (Perludem) regarding the provisions of Article 414 paragraph (1) of Law Number 7 of 2017 regarding General Elections, namely that political parties must meet the threshold for obtaining a vote of at least 4% of the number of valid votes nationally to be included in determining the acquisition of seats for members of the DPR, however, the constitutional interpretation of the decision does not cancel the parliamentary threshold of 4%, but rather the interpretation of the decision providing legitimacy that the Constitutional Court decides on conditional constitutionality. The conditional constitutional decision contains a constitutional interpretation that the 4% parliamentary threshold remains valid for both the 2024 DPR elections and the 2029 DPR elections, as long as the determination of the threshold is not based on methods, arguments and requirements as determined in the Constitutional Court decision.